Elucidating insect-virus associations in black pepper: Mealybug and tending ant influences on viral incidence in East Malaysia, Borneo - Buang, Marthiuz Ghany; Aman-Zuki, Ameyra; Adam, Nur Azura; Sartiami, Dewi; King, Patricia Jie Hung; Yaakop, Salmah; Mohammed, Muhamad Azmi (Elsevier, 2025)
Piper nigrum, a key agricultural commodity in Sarawak, East Malaysia, is highly susceptible to the Piper yellow mottle virus (PYMoV), a badnavirus transmitted by mealybugs. This study aimed to identify the mealybug and tending ant species associated with black pepper plantations in Sarawak and assess the presence of PYMoV in mealybugs. Insects were collected from four divisions namely Kuching, Sibu, Bintulu, and Miri between 2020 and 2022. Species identification was performed using morphological and DNA barcoding techniques, while molecular methods were employed to detect PYMoV. Seven mealybug species were identified: Planococcus minor, Ferrisia virgata, Dysmicoccus lepelleyi, Planococcus sp., Pseudococcus sp., Phenacoccus sp., and Exallomochlus sp., with percentage identity ranging from 94.05 % to 100 %. Additionally, 14 tending ant species were identified, including Tapinoma indicum, Meranoplus bicolor, Anoplolepis gracilipes, Pheidole sauteri, Iridomyrmex anceps, Tetramorium cognatum, Crematogaster rogenhoferi, Camponotus sp., Dolichoderus sp., Leptogenys sp., and four distinct Crematogaster species, with accuracies between 85.29 % and 100 %. PYMoV was detected in 6.58 % of the mealybugs, with P. minor and Phenacoccus sp. identified as hosts, the latter being a novel discovery. No significant association was found between specific mealybug species and PYMoV prevalence (p = 0.99), suggesting that other factors may influence viral transmission. However, a strong positive correlation (r = 1.00, p < 0.05) was observed between ant presence and mealybug infestation, indicating that ants may facilitate mealybug dispersal. These findings highlight the necessity for continuous surveillance of mealybugs and tending ants to mitigate the spread of PYMoV and protect black pepper cultivation in Sarawak.